Genotypic Profiling and Tailored Therapeutic Strategies for Enhanced Management of Endodontic Infections - Asha Kiran Panda,; Sudipta Maity,; Bibhuti Prasad Barik, (The Bioscan, 2025)
Background: Persistent endodontic infections involving bacteria such as Staphy- lococcus aureus, Klebsiella pneumoniae, and Salmonella enterica present signifi- cant treatment challenges due to microbial diversity and resistance complexities within the root canal system. Traditional diagnostic methods often lack the preci- sion needed to identify specific strains and understand their pathogenic potential, which limits the effectiveness of treatment. Aims and Objectives: This study aims to enhance diagnostic accuracy in endodontic infections by utilizing advanced genotypic identification through high- resolution metagenomic sequencing. It also seeks to develop a genotype-specific treatment protocol that integrates molecular data to guide precise, personalized antimicrobial therapies for improved clinical outcomes. Materials and Methods: Infected tissue samples from clinical cases were sub- jected to metagenomic sequencing, focusing on the 16S rRNA gene to identify bacterial strains. Phylogenetic analysis was conducted to assess evolutionary relationships and detect genetic markers associated with pathogenicity and resis- tance. Based on genotypic data, a tailored treatment protocol was formulated to match the specific microbial composition of each infection. Results: The genotypic analysis revealed distinct genetic markers linked to virulence and resistance across the bacterial isolates, which enabled precise identification of pathogens at the species level. The tailored treatment proto- col, informed by the genotypic profile of each infection, demonstrated potential to optimize pathogen eradication and reduce recurrence rates, thus improving patient outcomes. Conclusion: This study highlights the value of molecular diagnostics in enhanc- ing diagnostic precision and enabling genotype-guided therapies for endodontic infections. By integrating comprehensive genotypic data into treatment plan- ning, clinicians can adopt individualized approaches that improve efficacy, reduce treatment failures, and optimize patient recovery in complex endodontic cases.